ChemInform Abstract: Nickel‐Catalyzed Chelation‐Assisted Direct Arylation of Unactivated C(sp3)—H Bonds with Aryl Halides. Issue 37 (16th September 2014) - Li, Mingliang; Dong, Jiaxing; Huang, Xiaolei; Li, Kaizhi; Wu, Qian; Song, Feijie; You, Jingsong
Abstract The nickel‐catalyzed monoarylation of amides (I) with corresponding aryl iodides (II) and (IV) gives rise to desired β‐arylated derivatives (III) and (V), resp., as single products.